On the nature of hydrogen bonding between the phosphatidylcholine head group and water and dimethylsulfoxide - Dabkowska, A; Lawrence, M; McLain, SE; Lorenz, C (2013)
Molecular dynamics simulations are used to provide a detailed investigation of the hydrogen bond networks around the phosphatidylcholine (PC) head group in 1,2-dipropionyl-sn-glycero-3-phosphocholine in pure water, 10 mol.% and 30 mol.% dimethylsulfoxide (DMSO)-water solutions. Specifically, it is observed that DMSO replaces those water molecules that are within the first solvation shell of the choline, phosphate and ester groups of the PC head group, but are not hydrogen-bonded to the group. The effect of the presence of DMSO on the hydrogen bond network around the PC head groups of the lipid changes with the concentration of DMSO. In comparison to the hydrogen bond network observed in the pure water system, the number of hydrogen-bonded chains of solvent molecules increases slightly for the 10 mol.% DMSO system, while, in the 30 mol.% DMSO system, the number of hydrogen-bonded chains of solvent molecules decreases. © 2012 Elsevier B.V. All rights reserved.